بەها پەروەردەییەکان لە شیعری منداڵان بە نموونەی شیعری ساڵانی ( ٢٠١٠- ٢٠٢٠) - عیسی, پ.د. هاوژین صلیوه‌; حمدامین, ئه‌ژین عزالدین (Sulaimani Journal for Humanities, 2023)
Children's poetry is an important component of the literary elements, as it occupies a wide space in the literature. The history of children's poetry is consistent with motherhood and childbirth, and then gradually expanded until poets and writers became interested in it as a type of literature. They used a specific language, especially in the world of children, and referred to topics that correspond to the development of thought. Children and their knowledge and intelligence according to the stages of their lives. In addition to what poetry contains of educational value and purposeful content. The definition of values differs according to the science they contain, but educational values include all purposes that stem from the general goals of education for the purpose of transferring events and values to the future generation. Poetry is not devoid of a message, as each poetry carries with it a message of its own, but the important thing here is that children’s poets try to convey the most beautiful and greatest educational value in their poetry through the use of appropriate language and wide imagination, because children generally desire imaginary things. Our current research under the title "Educational values in children's poetry between 2010 to 2020" is an evaluation and identification of educational values in the collections of poetry presented to children during this period.
Keywords: ئهدهبی منداڵانChildren; s literature بەها Value پهروهرده Education شیعری منداڵان Children; s poetry